Activity Test of The Combination Papaya Leaf Extract (Carica papaya L.) and Soursop Leaf Extract (Annona muricata L.) on Decreasing Blood Glucose Levels in Rats (Rattus norvegicus) - Arfiani, Putri Yuni; Almeida, Maria; Arifian, Hanggara; Arief, Maryam Jamila; Herman, Herman (Journal of Pharmaceuticals and Natural Sciences, 2024)
Diabetes mellitus (DM) is one of the most common health disorders and its prevalence rate is increasing every year. Natural compounds can be an alternative treatment for DM. Previous re-search reports for papaya leaves (Carica papaya L.) and soursop leaves (Annona muricata L.) showed activity in lowering blood glucose levels when used alone. Therefore, in this study, the two samples were combined to lower blood glucose levels. Both leaves were extracted using the decoction method. This study aims to identify secondary metabolite compounds in papaya leaf extract (Carica papaya L.) and soursop leaf extract (Annona muricata L.), then continued with determining the activity and effectiveness of lowering blood glucose levels. The results of the identification of secondary metabolite compounds showed several groups of compounds such as flavonoids, saponins and tannins. The combination of papaya leaf extract and soursop leaf extract showed a decrease in blood glucose levels. In more detail, EDPS 1:2 and EDPS 2:1 were statistically significant against negative controls. EDPS 1:2 showed the most effective percentage reduction in blood glucose levels at 22.72%